Prayers for the people : things we didn't know we could say to God - Stokes, Terry J. (Convergent, 2021)
"A collection of timely, stirring, and witty short-form prayers (aka collects) that give language to the full breadth of our everyday experiences-from joy to sorrow, and everything in between. In his debut collection of prayers, Terry Stokes names all the things we didn't know we could pray for: student loan cancellation; strength when we're about to make small talk; restraint when we have the opportunity to be petty. The collection features an impressive range of humor and inspiration, but also spans prayers of lament and solidarity. These tender, convicting, and entertaining prayers invite readers to see the wonders, joys, and access to God available in any scenario we may encounter. By putting words to the emotions and needs that lay beneath our petitions, our celebrations, and our resistance, Stokes's prayers make for an engaging and heartfelt read that will delight and encourage any person of faith in the modern age"--